The Use of the Laws of Physics Allows a Person who has Died, for Example, as a Result of an Accident or Crime, to be Brought Back to Life - Alexandrovich, Antonov Alexander (European Journal of Applied Sciences, 2025)
In the article it is suggested that due to the fast (faster than the Earth rotates) movement on the Earth through time zones to carry out accessible to people travelling (for example, by plane) both in the past and in the future time. An example of realisation of such time travel routes is given, allowing to bring back to life people who died as a result of an accident or criminal humans activity.